Denmark - on your bike! The national bicycle strategy. - (:unkn) unknown (My University, 2014)
The new national bicycle strategy was launched to encourage more people to cycle. Although Denmark is one of the leading cycling countries, fewer Danes use their bicycles than in the past. The trend for cycling in Denmark must be reversed so that more people again choose the bicycle every day for work, education and leisure activities. It's a matter of focusing on more cycling and continuing to find new solutions that make it attractive to choose the bicycle as a means of transport, for both adults and children. Once the framework is established so that it is safe and secure to take the bicycle, people will have the opportunity to make the healthy choice. The new national bicycle strategy will focus on both everyday cycling, school cycling and recreational cycling to ensure that Denmark gets on the bike.
Keywords: Individualverkehr; Fahrradverkehr; Verkehrspolitik; Fahrradförderung; Fahrradnutzung; Fahrradbenutzung; Radverkehrspolitik; Strategie; Radverkehrssicherheit; Fahrradtourismus